Phytochemical constituents of Camellia osmantha fruit cores with antithrombotic activity. Issue 5 (21st March 2022) - Yang, Li; Xie, Gui‐Liang; Ma, Jin‐Lin; Huang, Xiao‐Qiong; Gu, Yao; Huang, Lei; Chen, Hai‐Yan; Ouyang, Xi‐Lin
Abstract: Camellia osmantha is a new species of the genus Camellia and is an economically important ornamental plant. Its activity and ingredients are less studied than other Camellia plants. This study investigated the antithrombotic effect and chemical components of C. osmantha fruit cores using platelet aggregation assays and coagulation function tests. The cores of C. osmantha fruits were extracted with ethanol to obtain a crude extract. The extract was dissolved in water and further eluted with different concentrations of methanol on an MCI resin column to obtain three fractions. These samples were used for antithrombotic activity tests and phytochemical analysis. The results showed that the extract and its fractions of C. osmantha have strong antithrombotic activity, significantly reducing the platelet aggregation rate and prolonging the thrombin time (TT). The total saponins, flavonoids, and polyphenols in the active fractions may be responsible for the antithrombotic activity. The chemical constituents were analyzed by ultra‐performance liquid chromatography‐quadrupole time‐of‐flight mass spectrometry (UPLC‐QTOF/MS). Twenty‐three compounds were identified rapidly and accurately. Among them, ellagic acid, naringenin, and quercetin 3‐ O ‐glucuronide may be important antithrombotic constituents. Furthermore, interactions between these compounds and the P2Y1 receptor were investigated via molecular modeling, because the P2Y1 receptor is a key drug target of antiplatelet aggregative activity. The molecular docking results suggested that these compounds could combine tightly with the P2Y1R protein. Our results showed that C. osmantha fruit cores are rich in polyphenols, flavonoids, and saponins, which can be developed into a promising antithrombotic functional beverage for the prevention and treatment of cardiovascular and cerebrovascular diseases. Abstract : The extract of C. osmantha has good antithrombotic activity. The total saponins, flavonoids, and polyphenols may be responsible for the antithrombotic activity. Ellagic acid, naringenin, and quercetin 3‐ O ‐glucuronide combined tightly with the P2Y1R protein may be important antithrombotic constituents. C. osmantha fruit cores can be used as a promising antithrombotic functional beverage.